Vitamin D C3-epimer levels are proportionally higher with oral vitamin D supplementation compared to ultraviolet irradiation of skin in mice but not humans. Issue 186 (February 2019) - Ghaly, Simon; Bliuc, Dana; Center, Jacqueline R.; Clarke, Michael W.; Jones, Anderson P.; Trend, Stephanie; Kermode, Allan G.; Neale, Rachel E.; Hart, Prue H.
Graphical abstract: Highlights: In mice, oral vitamin D compared to UV irradiation leads to a greater proportion of 25-hydroxy vitamin D3 as epimers. Exposure of mice to UV radiation alters liver CYP2R1 and GC protein gene expression and kidney CYP24A1 gene expression. Using samples from two human clinical trials, the proportion of 25(OH)D3 as epimers is significantly less compared to mice. The proportion of 25(OH)D3 as epimers is not different with UV-irradiation compared to oral vitamin D in humans. Abstract: A proportion of circulating 25-hydroxy vitamin D3 (25(OH)D3) ) undergoes epimerization to form C3-epi 25(OH)D3 and C3-epi 1, 25(OH)2 D3 . These epimers have less calcaemic activity than non-epimerized metabolites and are not differentiated by many immunoassays when reporting total 25(OH)D3 levels. This study aimed to compare the effect of exposure to ultraviolet radiation (UVR) and oral vitamin D3 supplementation on vitamin D C3-epimer levels. C57Bl/6 female mice were fed either vitamin D-sufficient (vitamin D3 2000 IU/kg) or -deficient diets (no vitamin D3 ) for 4 weeks. Among the vitamin D-deficient group, the shaved backs of half were irradiated daily for 4 days with 1 kJ/m 2 UVR, followed by twice weekly irradiation for 4 weeks. Despite similar 25(OH)D3 levels, the UV-irradiated group had a lower proportion of C3-epi 25(OH)D3 at week 7 (p < 0.05) and week 9 (p < 0.01). C3-epimer concentrations and %C3-epi 25(OH)D3 were also analysed in serum samples from two human clinical trials. These trials investigated the effect of high dose oral vitamin D3 supplementation and narrowband UVB phototherapy, respectively. Serum 25(OH)D3 and the %C3-epi 25(OH)D3 levels measured at 12 months after oral vitamin D3 supplementation were not significantly different to those measured at the time of maximal effect of phototherapy (2 months). Thus, the proportion of 25(OH)D3 that undergoes epimerization is greater with oral vitamin D3 supplementation than exposure to UVR in mice, but not in humans. This important difference between human and murine vitamin D metabolism warrants consideration when interpreting animal studies.